PENILAIAN INVESTASI MODAL KERJA PADA PERUSAHAAN FINANCIAL UNCONSTRAINTS - rahayu, Rika; Zahro, Maratus (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2022)
This study identifies the assessment of investasi modal kerja in financial constraints on firm value in Indonesia. The dependent variable in this study is the value of the firm. Several components include independent variables on investasi modal kerja, such as: current income, current cash, current changes in fixed assets, current interest, current net working capital, current dividend payout ratio, next year's income, next year's cash, next year's changes in fixed assets. , the following year's interest, the following year's net working capital, the following year's dividend payout ratio. The control variable in this study is the debt to equity ratio. The sample of this study used trading companies registered in Indonesia. The results of this study are several components of investasi modal kerja in the value of firm, namely; current income and net capital for the following year.